Association of Vitamin K Status Combined With Vitamin D Status and Lower‐Extremity Function: A Prospective Analysis of Two Knee Osteoarthritis Cohorts. Issue 8 (29th May 2018) - Shea, M. Kyla; Loeser, Richard F.; McAlindon, Timothy E.; Houston, Denise K.; Kritchevsky, Stephen B.; Booth, Sarah L.
Abstract : Objective: Vitamins K and D are important for the function of vitamin K–dependent proteins in joint tissues. It is unclear whether these nutrients are mutually important to functional outcomes related to knee osteoarthritis (OA). We evaluated the association of vitamin K and D sufficiency with lower‐extremity function in the Health, Aging and Body Composition knee OA substudy (Health ABC) and conducted a replication analysis in an independent cohort, the Osteoarthritis Initiative (OAI). Methods: In Health ABC (60% female, mean ± SD age 75 ± 3 years) baseline nutrient status was measured using circulating vitamin K and 25‐hydroxyvitamin D (25[OH]D). Lower‐extremity function was assessed using the Short Physical Performance Battery (SPPB) and usual 20‐meter gait speed. In the OAI (58% female, mean ± SD age 61 ± 9 years), baseline nutrient intake was estimated by food frequency questionnaire. Lower‐extremity function was assessed using usual 20‐meter gait speed and chair stand completion time. Multivariate mixed models were used to evaluate the association of vitamin K and D status and intake with lower‐extremity function over 4–5 years. Results: Health ABC participants with sufficient plasma vitamin K (≥1.0 nmoles/liter) and serum 25(OH)D (≥50 nmoles/liter) generally had better SPPB scores and faster usual gait speed over followup ( P ≤ 0.002). In the OAI, sufficient vitamin K and vitamin D intake combined was associated with overall faster usual gait speed and chair stand completion time over followup ( P ≤ 0.029). Conclusion: Sufficient vitamin K status combined with sufficient vitamin D status was associated with better lower‐extremity function in 2 knee OA cohorts. These findings merit confirmation in vitamin K and D co‐supplementation trials.